A study of the scientific information needs and literature use of researches at the Aquaculture Department, Southeast Asian Fisheries Development Center, Tigbauan, Iloilo, Philippines - Orejana, Rebecca Dacanay, 1948-
Data were gathered by means of a questionnaire submitted to a group of 156 researchers in the disciplines of aquaculture and fisheries. Analysis of 623 references cited in 76 published and unpublished research reports and research papers prepared by SEAFDEC international trainees and researchers, and analysis of statistics of library loans supplemented the data obtained from the answers of 109 respondents.